VD_FINDINFO HC / 2010 / 152 vom 11. März 2010 - VD Tribunal cantonal (2010)
INTERDICTION DE L'ARBITRAIRE, EXPULSION DE LOCATAIRE, CHOSE LOUÉE, RESTITUTIONEN GÉNÉRAL, DÉPENS | 457 CPC, 9 Cst., 23 LPEBL, 29 LPEBL